Pfeiffer-like Syndrome With Holoprosencephaly: A Newborn With Maternal Smoking and Alcohol Exposure - Pen-Hua Su; Jia-Yuh Chen; Inn-Chi Lee; Yan-Yan Ng; Jui-Ming Hu; Suh-Jen Chen (Pediatrics and Neonatology)
We report the case of a female infant with Pfeiffer-like syndrome and holoprosencephaly. She had a cloverleaf skull, ocular proptosis, broad thumbs and halluces, and variable accompanying anomalies compatible with Pfeiffer syndrome. She also displayed microcephaly, short palpebral fissures, and a smooth philtrum, which are clinical signs consistent with fetal alcohol syndrome. She suffered from multiple congenital anomalies and died at 41 days of age. Cardio-pulmonary failure, brain abnormalities, prematurity, and multiple complications contributed to her death. The patient displayed normal chromosomal numbers and type. DNA analysis did not reveal fibroblast growth factor receptor (FGFR) genes FGFR1, FGFR2, FGFR3 or TWIST gene mutations. We review the previous reports of Pfeiffer syndrome and holoprosencephaly and describe our infant patient with Pfeiffer-like syndrome, holoprosencephaly, and heavy in utero maternal alcohol and smoking exposures.